2022
DOI: 10.1371/journal.pone.0263431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated reproductive health lesson materials in a problem-based pedagogy on soft skills for safe sexual behaviour among adolescents: A school-based randomized controlled trial in Tanzania

Abstract: Background Adolescents are currently becoming sexually active before their 18th birthday during which they have to battle with unsafe sexual behaviours, teenage pregnancies, sexually transmitted infections (STIs), and school dropouts. The trend is linked with low soft skills (self-esteem and assertiveness skills) for them to make informed, reasoned, and responsible decisions over sexual activities. This study designed and tested the effect of integrated reproductive health (RH) lesson materials in a problem-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In this study, an EPPM was applied to assess the response of students to the condom use message for HIV/AIDS prevention among high school and preparatory students in Bahir Dar city, Ethiopia. 26,38,39 In this study, 60.9% of the respondents provided danger control responses. This is higher than a study conducted in Hosanna, Ethiopia among high school students aimed to evaluate the effectiveness of being faithfulness message for HIV prevention, which showed that 48.1% of the respondents were in danger control response.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, an EPPM was applied to assess the response of students to the condom use message for HIV/AIDS prevention among high school and preparatory students in Bahir Dar city, Ethiopia. 26,38,39 In this study, 60.9% of the respondents provided danger control responses. This is higher than a study conducted in Hosanna, Ethiopia among high school students aimed to evaluate the effectiveness of being faithfulness message for HIV prevention, which showed that 48.1% of the respondents were in danger control response.…”
Section: Discussionmentioning
confidence: 75%
“…In this study, an EPPM was applied to assess the response of students to the condom use message for HIV/AIDS prevention among high school and preparatory students in Bahir Dar city, Ethiopia. 26,38,39…”
Section: Discussionmentioning
confidence: 99%
“…Based on the recommendations from previous scholars [25][26][27], The following procedures were performed to determine the minimum sample size for the study using the formula by Cochran 1977 [28].…”
Section: Study Population and Sample Size Determinationmentioning
confidence: 99%
“…Several studies state that children will face adolescence and need to be instilled in the values and skills of assertiveness, self-esteem, and faithfulness in building social life in adolescence. The role of parents in this case is to support making the right decisions, daring to refuse things that lead to negative relationships at a young age (Millanzi et al, 2022). It was also added that the search for information related to accidents and injuries had a statistical correlation with the education level of parents (p-value = 0.005), this can be proven based on statistical analysis that parents who often access information about accidents and injuries to their children are parents with high school education.…”
Section: Figure 1 Frequency Of Parents In Seeking Children's Health I...mentioning
confidence: 99%